2018
DOI: 10.1089/sur.2018.093
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Surgeons' Double-Gloving Practice

Abstract: Less than half of the respondents practice double gloving, the main reason being self-protection. The most common reason for not wearing them was that they are required only for special cases. There was notable association between wearing double gloves and orthopedic surgery. Most needle-prick injuries occurred while wearing single gloves. We believe increasing awareness of the benefits of double gloving might change the practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
0
1
Order By: Relevance
“…This result might be attributed to the lack of knowledge and awareness among the ED staff about using personal protective equipment (PPEs). Our findings are not in line with the findings reported by Aljehani et al [ 13 ], who indicated that requiring double-gloving for special cases is the most factor influencing the use of double-gloving.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result might be attributed to the lack of knowledge and awareness among the ED staff about using personal protective equipment (PPEs). Our findings are not in line with the findings reported by Aljehani et al [ 13 ], who indicated that requiring double-gloving for special cases is the most factor influencing the use of double-gloving.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the non-successful conversion to double-gloving might be explained by the fact that about half of the respondents believed that double-gloving is decreasing their hand sensation, which could be affecting the medical procedures they are performing and hence causing specific medical errors. These findings are consistent with the findings reported by AlJehani et al [ 13 ], who found that a great majority of surgeons in King Abdul-Aziz Hospital were successful in conversion to double-gloving.…”
Section: Discussionsupporting
confidence: 93%